Učinek tarčne radiofrekvenčne terapije na bolečino in gibljivost ramenskega sklepa pri pacientih z zamrznjeno ramo - Štabuc Žonta, Anja (Rehabilitacija (Ljubljana), 2024)
Background: Primary adhesive capsulitis of shoulder, also known as »frozen shoulder«, is a disease that manifests itself with increasing pain and limitation of movement in the shoulder joint. It is one of the main causes of severe pain in the middle-aged and elderly population, and its incidence is increasing. So far, there is no consensus regarding the most effective method of treatment. Targeted high-frequency therapy is a therapeutic technique that combines contact diathermy and electrotherapy. The electromagnetic frequency used originates from the radio frequency spectrum. The therapy is increasingly used in the treatment of various musculoskeletal disorders. The purpose of this research was to see if targeted high-frequency therapy can improve mobility and reduce pain in patients with frozen shoulder in the short term. Methods: We included 12 patients with frozen shoulder in the study. We measured the range of motion of the shoulder joint in the direction of elevation through anteflexion, elevation through abduction, anteflexion, retroflexion, abduction, external and internal rotation using a goniometer, and assessed the intensity of shoulder pain with a visual analogue scale before the first and after the fifth targeted high-frequency therapy (five 15-minute sessions in three cycles, over a period of two weeks). Results: The mobility of the shoulder joint improved after five therapies, statistically significantly in the direction of elevation through anteflexion, elevation through abduction, external rotation and abduction. The average range of motion in the direction of anteflexion and retroflexion remained unchanged. For the movement of internal rotation, we found a slightly higher average value after therapy, but this was not statistically significant. The average value of shoulder pain at rest before and after therapy was close to zero. After five therapies, we found a statistically significant reduction in shoulder pain during activity. We also detected a statistically significant association between the reduction of pain and progress in terms of mobility for the retroflexion movement; the association was moderately strong. Conclusion: Targeted high-frequency therapy has a beneficial effect on reducing pain and improving shoulder joint mobility in patients with frozen shoulder, but further research is needed to draw definitive conclusions.
Keywords: adhesive capsulitis; adhezivni kapsulitis; bolečina; Bursitis; frozen shoulder; limitation of mobility; omejitev; Pain; Physical Therapy Modalities; rehabilitation; tarčna radiofrekvenčna terapija; targeted radiofrequency therapy; zamrznjena rama